Faktor-Faktor yang Berhubungan dengan Kualitas Hidup Pasien Geriatri yang Menjalani Hemodialisis - Mohammad, Nurhidayat; Soejono, Czeresna Heriawan; Lydia, Aida; Rinaldi, Ikhwan; Syafiq, Muhammad; Wardoyo, Elizabeth Yasmine (UI Scholars Hub, 2025)
Introduction. The decline in quality of life among geriatric patients undergoing hemodialysis has a negative impact on treatment adherence, physical functioning, dietary patterns, and mortality. This study was conducted to assess the quality of life of geriatric hemodialysis patients and its association with comorbidities, functional status, frailty, sarcopenia, nutritional status, depression, hemoglobin levels, hemodialysis vintage, vascular access, and hemodialysis adequacy. Methods. This study employed a cross-sectional design with primary data collection. Consecutive sampling was used to recruit participants. The study was conducted at the hemodialysis units of Cipto Mangunkusumo National General Hospital (RSCM), Persahabatan National General Hospital (RSP), and Fatmawati National General Hospital (RSF) from June 2024 to August 2024. The inclusion criteria were patients aged ≥60 years undergoing maintenance hemodialysis. Exclusion criteria were unstable clinical condition, cognitive or mental impairment, and refusal to participate. Quality of life was assessed using the EQ-5D-5L instrument. Data on medical history and laboratory findings were obtained from hospital medical records. Bivariate analysis was performed using the Mann–Whitney U test for comorbidities, sarcopenia, depression, hemoglobin level, vascular access, and dialysis adequacy; the Kruskal–Wallis test for frailty, functional status, and nutritional status; and Spearman’s correlation for hemodialysis vintage. Multivariate analysis was conducted using linear regression to identify factors associated with reduced quality of life. Results. A total of 124 subjects (mean age 67 years) were included in this study. The mean EQ-5D-5L index score was 0.76 (IQR 0.63–1.00), while the mean VAS score was 70. The majority of subjects (75%) reported no difficulties in self-care or daily activities. Functional status (p < 0.0001) and depression (p < 0.002) were significantly associated with the quality of life in geriatric patients undergoing hemodialysis, with an adjusted R² value of 0.642. Conclusions. Geriatric patients undergoing HD at RSCM, RSP, and RSF had an average EQ-5D-5L index score of 0.76 (out of 1.000), and 75% of the patients reported no issues with self-care and daily activities. Functional status and depression have been proven to play a significant role in determining their quality of life.